2009
DOI: 10.1007/s10484-009-9102-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Efficacy of Connectivity Guided and Symptom Based EEG Biofeedback for Autistic Disorders

Abstract: Autism is a neurodevelopmental disorder characterized by deficits in communication, social interaction, and a limited range of interests with repetitive stereotypical behavior. Various abnormalities have been documented in the brains of individuals with autism, both anatomically and functionally. The connectivity theory of autism is a recently developed theory of the neurobiological cause of autisic symptoms. Different patterns of hyper- and hypo-connectivity have been identified with the use of quantitative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 66 publications
2
27
0
1
Order By: Relevance
“…Positive gains have also been documented for individuals with AS (Coben & Myers, 2010;Knezevic et al, 2010;Kouijzer et al, 2010;Thompson et al, 2010). More specifically, Thompson et al (2010) reported significantly marked improvements in attention (both auditory and visual) and impulsivity.…”
Section: Nfb Trainingmentioning
confidence: 82%
See 2 more Smart Citations
“…Positive gains have also been documented for individuals with AS (Coben & Myers, 2010;Knezevic et al, 2010;Kouijzer et al, 2010;Thompson et al, 2010). More specifically, Thompson et al (2010) reported significantly marked improvements in attention (both auditory and visual) and impulsivity.…”
Section: Nfb Trainingmentioning
confidence: 82%
“…More specifically, Thompson et al (2010) reported significantly marked improvements in attention (both auditory and visual) and impulsivity. Coben and Myers (2010) reported significant improvements with social interaction and communication. With documented improvements across all areas of difficulty, there is increased potential for longterm management of the disorder.…”
Section: Nfb Trainingmentioning
confidence: 96%
See 1 more Smart Citation
“…The reliability and validity of quantitative EEG (qEEG) have been sufficiently assessed and confirmed (Thatcher, 2010). We have previously shown qEEG data to be useful in impacting outcome of NF intervention for children on the autistic spectrum (Coben & Myers, 2010;Coben & Padolsky, 2007). All EEG data was subjected to manual artifacting procedures conducted by a professional with more than 30 years' experience.…”
Section: Methods Participant Characteristicsmentioning
confidence: 99%
“…The primary premise of this approach is that localized cortical dysfunctions, or dysfunctional connectivity between localized cortical areas, correspond with a variety of mental disorders and presenting symptoms (Coben & Myers, 2010;Collura, 2010;Walker, 2010). When the EEG record of an individual is then compared to a normative database representing a sample of healthy individuals, the resulting outlier data (deviations of zscores from the mean) help link clinical symptoms to brain dysregulation (Thatcher, 2013).…”
Section: Normalization Model Of Qnfmentioning
confidence: 99%